Acupuncture for Treatment of Acute Vomiting in Children with Gastroenteritis and Pneumonia - Anders, E. F.; Findeisen, A.; Lode, H. N.; Usichenko, T. I. (Klinische Pädiatrie, 2012)
Acupuncture is successfully used to alleviate vomiting in children after general anesthesia. However there is no data on treatment of vomiting in children with gastroenteritis (GE) and pneumonia (PM).Descriptive analysis of 18 cases, where acupuncture was used as an individual therapy attempt to treat vomiting in children with GE or PM before starting the conventional antiemetic therapy. Feasibility and acceptance by patients and parents as well as the incidence of vomiting and use of antiemetic drugs after acupuncture were recorded.Acupuncture was feasible in all children and application of the indwelling needles was tolerated without fear. Side effects were not observed. 13 patients stopped vomiting immediately after the insertion of acupuncture needles, none of the patients required conventional antiemetic medication.Acupuncture for the treatment of vomiting is feasible and acceptable. Suggested antiemetic effect should be examined in a randomized multicenter controlled trial.
Keywords: acupuncture; vomiting; children; gastroenteritis; pneumonia; individual therapy attempt